Franchise business as a generator of development in Central Europe - Suzana Baresa; Zoran Ivanovic; Sinisa Bogdan (UTMS Journal of Economics, 2017)
The franchise in the global marketplace enables many globally known brands. With its business concept, it enables integration, learning and acceptance of various cultural, historical, religious and other customs and habits. Consumers prefer a proven and expected standard product quality and services, no matter where they are, they expect and want the same quality provided by franchise companies (shops, restaurants, hotels, and others) of well-known brands in different places. It can be concluded that the franchise enables the transfer of business knowledge, experience and technology to an unlimited space. Franchise is largely present as a way of doing business in the world and it has an impact on national economies. Companies can use it as a strategic growth model, as a model for launching a whole new business. Since Croatia has enough potential to develop franchise business that is not sufficiently exploited, that potential could be largely exploited in addition to overcome certain problems. Conducting a systematic analysis of franchise business and development would contribute to this. This paper deals with basic concepts related to the franchise business, features and characteristics, advantages and disadvantages of franchise business, the impact it has on the national economy (US example), and a comparative analysis of the franchise business in Croatia compared to other Central European countries.
Keywords: G32; L14; M55; 330; know-how; brand; royality; franchise